An Analysis of Slang Used in Wednesday TV Series 2022 - Raflis, Raflis; Aulya, Mesi (Fakultas Sastra Universitas Ekasakti, 2024)
This research is conducted to discuss the types of slang words and the functions of the slang words in the Wednesday TV Series. The researcher used theory about types of slang proposed by Allan and Burridge (2006) and Bloomfield and Guth (2014) to classify the types of slang and to analyze the function of slang. This research was conducted by using Descriptive Qualitative Research. The technique used to collect the data was the taking notes technique and to analyze the data was the document analysis. Based on the data analysis it was found seven types of slang found in Wednesday TV Series which is fresh an creative with a total 11 data, flippant with a total 22 data, imitative with a total 7 data, clipping with a total 7 data, abbreviation with a total 4 data, interjection with a total 2 data, and shortened forms with a total 2 data. Furthermore, there are seven function of slang found in Wednesday TV Series, they are to address with a total 8 data, to form intimate atmosphere with a total 9 data, to initiate relax conversation with a total 19 data, to express impression with a total 9 data, to show intimacy with a total 2 data, to reveal anger with a total 3 data, and to humiliate with 5 data.